Early cretaceous multi-stage extension in the North Dabie complex in the eastern central China: insights from structural and geochronological data - Huang, Peng; Yan, Zhen; Xiao, Wenjiao; Sang, Miao; Mao, Qigui; Abuduxun, Nijiati (Frontiers in Earth Science, 2024)
A dominantly NW-SE directed extensional tectonics in the Early Cretaceous significantly reworked the Late Permian-Triassic orogenic framework of the Dabie orogenic belt. The North Dabie complex (NDC) is the principal domain recording this tectonic event. However, the precise structure-kinematic architectures, particularly those observed in the ductile regime, along with the respective time scales for different extensional stages, have not been adequately established. This significantly impedes our comprehensive understanding of the extensional style and deformation history in the North Dabie complex. To better address these issues, we conducted a systematic structural study and LA-ICP-MS zircon U-Pb dating of the pre-, syn-, and post-kinematic intrusions and syn-kinematically metamorphosed high-grade gneisses/migmatites of the NDC. Our results demonstrate that the extensional deformation in the NDC may initiate at ca. 144 Ma, which is characterized by a pervasive NW-SE oriented coaxial plastic flow in the ductile regime of the middle-lower crust. A large-scale detachment processing zone subsequently started activating at ca. 140 Ma at the upper-middle level of the middle crust, and concentratedly accommodated the extensional strain by top-to-NW ductile shearing. Locally, there was uprising of sub-magmatic flow in the atatexite-diatexite from the deeper lower crust taking place in the manner of top-to-outward shearing as early as ca. 137 Ma. This composite process of extension manifests vertical strain partitioning across the ductile middle-lower crusts and progressive strain localization during the lithospheric thinning. The NW-SE orientation dominated extensional tectonics was strongly driven by the westward subduction of the Paleo-Pacific oceanic plate during the Late Mesozoic.